PERSEPSI DAN TINDAKAN AWAL KELUARGA TERHADAP GEJALA DEMAM DI DAERAH KEJADIAN LUAR BIASA (KLB) DEMAM BERDARAH DENGUE DI PUSKESMAS PALARAN SAMARINDA - Muji Sutrisno; Rahmat Bakhtiar; Mahyati Sari Zulfa; Chrisna Wahyu Hardian; Adeline Arung Labi; Opiansyah Opiansyah (STIKes Hang Tuah Pekanbaru, 2020)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease because of dengue virus transmission through the bite of Aedes aegypti. Dengue cases in Palaran has increased sharply from January to November 2018. There were 218 morbidity of this number of cases with 1 mortality case. Meanwhile in 2017, the number of morbidity cases just 28 cases and no cases of death. Objective : To know the perception and early action of family for fever symptoms on the outbreak of Dengue Hemorrhagic Fever in Palaran Public Health Center Samarinda. Method: Quantitative descriptive study with 102 respondents who obtained directly through perception questions and early actions of families against fever symptoms on an area of the outbreak of dengue hemorrhagic fever in Palaran Public Health Center Samarinda period from October to December 2018. Results: Families with the initial perception of fever due to other diseases (77.5%), the initial perception no danger fever (63.7%), the initial act of family medicine came to the health center (30.47%) Conclusion: Families perception and early action against fever symptoms on the outbreak events of dengue hemorrhagic fever in Palaran Public health center Samarinda period from October to December 2018 found family with the initial perception of another fever illness, initial perception of fever is not the danger, the initial act of family medicine at the most come to the health center. Keywords: DHF, outbreak, perception, risk, early action